Church and poverty in South Africa: Historical analysis and missional ecclesiology - Prinsloo, Christoffel B. (HTS teologiese studies, 2024)
Poverty remains a critical socio-economic challenge in South Africa, deeply rooted in the country’s history of colonialism and apartheid. This article examines the multifaceted role of churches in poverty alleviation efforts in South Africa, spanning both historical and contemporary contexts. Through analysis of historical records and contemporary literature, it argues that while churches have significantly addressed poverty, a more comprehensive and transformative approach is needed. The study proposes adopting a missional ecclesiology framework to enhance the effectiveness of church-led poverty alleviation initiatives, offering insights into how churches can engage more deeply and sustainably in the fight against poverty.Contribution: This research contributes to existing scholarship by: (1) Providing a comprehensive historical analysis of church involvement in poverty alleviation in South Africa. (2) Critically examining challenges and opportunities in contemporary church-led poverty alleviation efforts. (3) Proposing missional ecclesiology as a framework for enhancing church-based poverty alleviation initiatives. (4) Offering practical recommendations for churches to address poverty within South Africa’s unique socio-economic context.